1992
DOI: 10.1177/097133369200400106
|View full text |Cite
|
Sign up to set email alerts
|

Anāsakti and Health: A Study of Non-attachment

Abstract: This study examined the health consequences of an indigenous concept "Anāsakti" which means non-attachment. The scale measuring anāsakti was based on the characteristics of a man of steady wisdom "the sthitaprajña", described in the Bhagvad Gītā. It was hypothesised that those higb on anāsakti would experience less distress and exhibit fewer symptoms of strain when faced with stressful life events. Results showèd tbat anāsakt subjects were less distressed and exhibited fewer symptoms of ill health. Anāsakti wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 9 publications
4
57
0
1
Order By: Relevance
“…Previous case studies suggest that large proportions of organisation members practising the TM technique contribute to improvements in organisational performance (Schmidt-Wilk, Alexander, & Swanson, 1996). Parde and Naidu (1992) report empirical evidence to show that people with a strong orientation to working sincerely without being preoccupied with the outcome experience less work-related stress. Misra (1989) found that effort orientation rather than concern for outcome leads to greater intrinsic satisfaction.…”
Section: Yoga and The Work Lifementioning
confidence: 95%
“…Previous case studies suggest that large proportions of organisation members practising the TM technique contribute to improvements in organisational performance (Schmidt-Wilk, Alexander, & Swanson, 1996). Parde and Naidu (1992) report empirical evidence to show that people with a strong orientation to working sincerely without being preoccupied with the outcome experience less work-related stress. Misra (1989) found that effort orientation rather than concern for outcome leads to greater intrinsic satisfaction.…”
Section: Yoga and The Work Lifementioning
confidence: 95%
“…Bible teaches that if anyone wants to fi nd one's life should lose it and there seems no other alternative (Luke 17:33, Bible 2007 ). Bhagavad Gita proposes that liberation and happiness can be attained through selfl ess and desire-less action (Pande and Naidu 1992 ). Evolutionary theories also confi rm this claim, highlighting that individuals who fail to enhance the survival of the other minimise their own survival in the long run (Simon 1993 ).…”
Section: Altruism and Well-beingmentioning
confidence: 95%
“…Also of relevance are indigenous philosophies and sayings which might be used to promote mental health, such as rnai pen rai, the Thai idea of acceptance meaning "never mind" and "don't worry" (Hollinger, 1965). A similar idea of non-attachment, anasakti, may be useful in India (Pande & Naidu, 1992).…”
Section: Cost~benefit Analysesmentioning
confidence: 97%